Evaluation and Treatment of Perioperative Corneal Abrasions - Kira L. Segal; Peter M. Fleischut; Charles Kim; Ben Levine; Susan L. Faggiani; Samprit Banerjee; Farida Gadalla; Gary J. Lelli (Journal of Ophthalmology)
Purpose. To evaluate perioperative risk factors for corneal abrasion (CA) and to determine current care for perioperative CA in a tertiary care setting. Methods. Hospital-based, cross-sectional study. In Operating Room and Post-Anesthesia Care Units patients, a comparison of cases and controls was evaluated to elucidate risk factors, time to treatment, and most common treatments prescribed for corneal abrasions. Results. 86 cases of corneal abrasion and 89 controls were identified from the 78,542 surgical procedures performed over 2 years. Statistically significant risk factors were age (P=0.0037), general anesthesia (P<0.001), greater average estimated blood loss (P<0.001), eyes taped during surgery (P<0.001), prone position (P<0.001), trendelenburg position (P<0.001), and supplemental oxygen en route to and in the Post-Anesthesia Care Units (P<0.001). Average time to complaint was 129 minutes. 94% of cases had an inpatient ophthalmology consult, with an average time to consult of 164 minutes. The most common treatment was artificial tears alone (40%), followed by combination treatment of antibiotic ointment and artificial tears (35.3%). Conclusions. Trendelenburg positioning is a novel risk factor for CA. Diagnosis and treatment of perioperative corneal abrasions by an ophthalmologist typically require three hours in the tertiary care setting.